2010
DOI: 10.1080/13546801003711350
|View full text |Cite
|
Sign up to set email alerts
|

Empathy, schizotypy, and visuospatial transformations

Abstract: Introduction-Adopting another person's visuospatial perspective has been associated with empathy, which involves adopting the psychological perspective of another individual. Both reduced empathy and abnormal visuospatial processing have been observed in those with schizophrenia and schizophrenia-related personality traits. In the current study, we sought to explore the relationship between empathy, schizotypy, and visuospatial transformation ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
76
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(86 citation statements)
references
References 81 publications
9
76
1
Order By: Relevance
“…Faster allocentric mental rotation was associated with increased schizotypy 87 and more specifically, negative schizotypy in women. 88 Findings are mixed with respect to self-other transformation involving egocentric mental rotation. Both impaired, 89 and enhanced 87,88,90 egocentric mental rotation performance have been reported in relation to elevated schizotypy.…”
Section: Imagery and Representationmentioning
confidence: 99%
See 2 more Smart Citations
“…Faster allocentric mental rotation was associated with increased schizotypy 87 and more specifically, negative schizotypy in women. 88 Findings are mixed with respect to self-other transformation involving egocentric mental rotation. Both impaired, 89 and enhanced 87,88,90 egocentric mental rotation performance have been reported in relation to elevated schizotypy.…”
Section: Imagery and Representationmentioning
confidence: 99%
“…88 Findings are mixed with respect to self-other transformation involving egocentric mental rotation. Both impaired, 89 and enhanced 87,88,90 egocentric mental rotation performance have been reported in relation to elevated schizotypy. These findings have implications for social cognitive abilities (see Cohen et al 15 ), notably theory-of-mind because one crucial aspect of mentalizing involves visuospatial perspective taking and simulation.…”
Section: Imagery and Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…The computerized version of the spatial cognition task was designed as per previous description (Thakkar and Park, 2010). The task focused on the ability of the subjects to take perspective from an egocentric or allocentric point of view and to rotate mentally the stimulus or their point of view.…”
Section: Spatial Cognition Taskmentioning
confidence: 99%
“…Among several domains of cognitive functions that have been examined in this disorder, spatial cognition is an area of active inquiry (Bose et al, 2014); interestingly, visuospatial abilities have been found to have intriguing interactions with several measures that are related to schizophrenia pathogenesis like empathy (Decety and Lamm, 2007), schizotypy (Thakkar and Park, 2010), and theory of mind (Bosia et al, 2012;Iacoboni and Dapretto, 2006). Models of visuospatial abilities posit two perspectives of visual space: allocentric (object-or environmentcentered) reference and egocentric (self-centered or body-centered) reference (O'Keefe and Nadel, 1978).…”
Section: Introductionmentioning
confidence: 99%